The Norton anthology of American literature (W. W. Norton & Company, 2012)
The Eighth Edition features a diverse and balanced variety of works and thorough but judicious editorial apparatus throughout. The new edition also includes more complete works, much-requested new authors, 170 in-text images, new and re-thought contextual clusters, and other tools that help instructors teach the course they want to teach.